Promoting the removal of fine particles and zero discharge of desulfurization wastewater by spray-turbulent agglomeration. (15th June 2020) - Sun, Zongkang; Yang, Linjun; Chen, Shuai; Bai, Lu; Wu, Xin
Graphical abstract: Highlights: The desulfurization wastewater spray and turbulent agglomeration were coupled. The PM2.5 and desulfurization wastewater were synergistically treated. The desulfurization wastewater spray enhanced fine particles agglomeration. Particles concentration after ESP was reduced by spray-turbulent agglomeration. The turbulent flow field promoted the complete evaporation of wastewater droplets. Abstract: The treatment of fine particles and desulfurization wastewater from coal-fired power plants is an important issue in the field of energy and environment. To promote the removal of fine particles and zero discharge of desulfurization wastewater, a novel treatment technology with the coupling of spray evaporation and turbulent agglomeration was proposed, and the effect of desulfurization wastewater spray on fine particles agglomeration and removal were investigated by experiment. The results showed that the spray-turbulent agglomeration system can effectively promote the agglomeration and removal of fine particles through capillary force and adhesion effect of crystals precipitated from the desulfurization wastewater droplets. After that the fine particles agglomeration efficiency was improved to 39.3%, which was 10.9% higher than single turbulent agglomeration, and the number and mass concentrations of fine particles after ESP reduced about 46.5% and 38.9%, respectively. In addition, the effect of turbulent agglomeration system on the evaporation of desulfurization wastewater was studied by simulation using CFD models, the motion trajectory, evaporation time and motion distance of spray droplets with different sizes were calculated. It indicated that turbulence can increase the relative velocity between droplets and flue gas, thus improving the heat and mass transfer rates of spray droplets in the evaporation process, so as to promote the evaporation of large-size droplets and shorten their motion distance required for complete evaporation. The average motion distance of spray droplets was shortened by 383 and 543 mm respectively at the diameter size of 110 and 120 μm.